2002
DOI: 10.1161/01.str.0000035734.61539.f6
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Training With Partial Body Weight Support and an Electromechanical Gait Trainer for Restoration of Gait in Subacute Stroke Patients

Abstract: Background and Purpose-The purpose of this study was to compare treadmill and electromechanical gait trainer therapy in subacute, nonambulatory stroke survivors. The gait trainer was designed to provide nonambulatory subjects the repetitive practice of a gait-like movement without overexerting therapists. Methods-This was a randomized, controlled study with a crossover design following an A-B-A versus a B-A-B pattern.A consisted of 2 weeks of gait trainer therapy, and B consisted of 2 weeks of treadmill therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
153
0
11

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(172 citation statements)
references
References 16 publications
(3 reference statements)
8
153
0
11
Order By: Relevance
“…Werner et al 21 reported some augmented improvement with Gait Trainer exercises, which was trending toward significance. We were, however, unable to reproduce these effects, probably as a result of different patient samples (in our group, median FAC 0 and Werner median FAC 1) rather than the type of orthosis device used.…”
Section: Discussionmentioning
confidence: 95%
“…Werner et al 21 reported some augmented improvement with Gait Trainer exercises, which was trending toward significance. We were, however, unable to reproduce these effects, probably as a result of different patient samples (in our group, median FAC 0 and Werner median FAC 1) rather than the type of orthosis device used.…”
Section: Discussionmentioning
confidence: 95%
“…The BWS s was reduced as soon as the patient could take his/her full weight, and the WS s was increased as soon as the patient could perform the task without overstraining and/or experiencing discomfort [5]. The physiotherapist involved in the GT treatment prepared the patients, chose the parameters, provided verbal feedback to the patient during the GT session, and manually controlled the patients' paretic knee, if needed.…”
Section: Protocol 1: Retrospective Studymentioning
confidence: 99%
“…The effectiveness of these devices has been investigated in patients with subacute [3][4][5] and chronic [6][7] stroke, but their overall efficacy has been questioned [8][9]. The absence of a general agreement may be due to differences among patients enrolled in these studies, as well as the lack of a unified approach to integrating these devices into rehabilitation programs [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations